The Effectiveness Of Draw Learning For Early Children's Visual Intelligence Growth - Nisa, Choirun (AKADEMIK: Jurnal Mahasiswa Humanis, 2023)
Parents are obliged to encourage and facilitate the growth of the child's ability, so that it becomes one of the provisions in wading through his adult life. So starting from an early age, many parents send their children to early childhood education, with the hope that the child can grow and develop well, especially in terms of intellectual and physical abilities. One of the curricula in kindergarten is learning to draw. This is done, as one of the relevant efforts for early childhood, to be able to optimize their visual and psychomotor intelligence. This research was conducted with the aim of looking at the effectiveness of learning to draw on the growth of visual intelligence in early childhood. So that it can be understood, that learning to draw is one of the subjects that needs to be included in the early childhood learning curriculum, because it has a positive impact on the development of children's intelligence. The research approach uses a quantitative approach with classroom action methods for early childhood students in the city of Tegal. The number of students observed was 100 people with a simple random sample technique. This research process was carried out for three months, with two actions, so that information about the effectiveness of an observation was obtained. The results of the study show that learning to draw is one of the media that is suitable for children's development, especially in terms of visuals. Because drawing itself is considered a game by the child, so without feeling like they are learning. In addition, essentially learning to draw encourages children to be able to improve their cognitive and psychomotor abilities, thereby stimulating children's creativity.